رأس المال الجريء الإسلامي: نموذج للتوفیق بین التمویل برأس المال الجريء والتمویل التشاركي الإسلامي - مجدوب, بحوصي; عریس , عمار (Finance and Business Economies Review, 2018)
Because of the inadequacy of traditional funding in providing the necessary financial resources for projects to ensure sustained, as a result, alternatives have emerged in new and more efficient and effective, can play an important role in investment funding and other traditional methods of financing, including venture capital funding and financing the system of participation, since each particular method and the nature of the private funding is distinguished from each other in the financing of various investment projects. Where is the essence of the problem this paper proposed in an attempt to study the components of funding venture capital and system participation, as well as to identify the financing risks in both systems, in addition to a comparison between funding the puppet regimes in terms of similarities and differences and the conclusion method allowing for the reconciliation between the two systems in funding